PENINGKATAN BERAT BADAN BALITA GIZI KURANG DENGAN PEMBERIAN MAKANAN NUTRISI TINGGI BERBAHAN BAKU TEMPE DAN KEMBANG KOL DI WILAYAH KERJA PUSKESMAS KABERE - Salma Salma; Haniarti Haniarti; Nurhaeda Nurhaeda (Jurnal Surya Muda, 2021)
Nutritional problems in Indonesia are getting more complex as the epidemiology transition occurs. According to reports of posyandu weighing activities at Kabere Puskesmas in 2020 there were 28 malnourished toddlers. The purpose of this study was to determine the increase in body weight of malnourished toddlers by providing high nutritional food made from tempeh and cauliflower in the working area of Kabere Public Health Center, Enrekang Regency. This type of research is a quantitative method with a quasi-experimental design with a non-equivalent control group design. The population is malnutrition under five in the working area of Puskesmas Kabere, The samples of this research were children under five who were malnourished, 14 under five who were given treatment and 14 children who were not given treatment for under-nutrition who were in the working area of the Kabere Community Health Center by calculating zcore, Data analysis was performed using the independent sample t-test with the help of the SPSS version 20 program. The location of this research was conducted in the working area of the Kabere Community Health Center. The research was conducted in July-August 2020.The results showed that the provision of high nutritional food made from tempeh and cauliflower could significantly increase body weight in malnourished children under five. So it is recommended that parents of toddlers provide adequate nutritional intake for under-nutrition children so that their nutritional status can continue to improve.